Intellectual capital and industrial firms’ growth: Evidence from Jordanian manufacturing listed firms - Mohammad Fawzi Shubita (Problems and Perspectives in Management, 2022)
This paper deals with the link between intellectual capital and the Jordanian industrial listed companies’ growth. This relationship is meaningful for the companies to enhance their interest in intangible assets. The study employed a regression analysis; independent variables are intellectual capital and intellectual capital components (human capital, structural capital, and capital employed). The current ratio is used as a control variable. The study sample, which contains 785 observations, is divided into the firms that generate positive ROE and those that generate negative ROE. The study sample included 77 Jordanian industrial listed firms during the period 2006–2020. The paper found that intellectual capital does not have a significant effect on industrial firm growth and its components do not have a significant effect on industrial firm growth. The main conclusions drawn from these results are that the return on equity do not affect the link between intellectual capital and industrial firms’ growth. The paper recommended applying the study models to other sectors like banks and service sectors and including other control variables like leverage and company size in these models.